PERANAN PENYULUH TERHADAP PENDAPATAN INDUSTRI RUMAH TANGGA BERBASIS UBI KAYU (Manihot utillisima Pohl) - Safitr Safitr; Asih Mulyaningsih; Ari Tresna Sumantri (JURNAL AGRIBISNIS TERPADU, 2015)
The study is conducted in the village of Teja Alas Pancaregang District of Serang which aims to findout how the role of agricultural extension is carried out on a group of women farmers, how theindustry earnings of cassava-based household and how the role of the extension of the income ofcassava-based industrial house. The research method used in this study is a survey method.Respondents who used the 25 women farmers or take a census. The data used in this study aresecondary and primary data. The data obtained were then analyzed with descriptive analysis, Likertscale, interval class, business income and cross tabulation. The research data generated in performingthe role of counselor duties and functions do counseling with 5 variable roles. produced the highestscores on the role of a motivator with high role category 15.2% of industry revenue score of 100 Levelof cassava-based household by 56% with the low category. Industrial household income of cassavabasedlow with the majority of roles in the high category. This dikarnakan no variables or otherfactors beyond the role of extension agents who have a relationship to the household income-basedindustries such as cassava selling prices, natural factors and capital.